Exploring multivariable calculus with Mathematica to accompany multivariable calculus - Cheung, Chi Keung (Wiley, 1996)
This innovative book funded by National Science Foundation, was developed as part of the calculus reform movement. It is problem driven and features exceptional exercises based on applications.